DENGUE OUTBREAK: A SYSTEM DYNAMICS APPROACH - Subyan, Amira Natasha; Abdul Jabar, Nur Fatin Afifi; Darlynie, Che Rohayu; Ahmad, Norazura (Journal of Technology Management and Business, 2018)
Dengue is an endemic disease that occurs across Malaysia with a large number of fatality cases being recorded each year. The Ministry of Health Malaysia has came out with the national dengue strategic plan in controlling the disease outbreak. Therefore, this study aims to develop a system dynamics model of dengue to help policy makers in simulating the effectiveness of the public health intervention. Simulation model can show the successes and failures of past policies, as well as predicting the consequences of selected policy proposals before their implementation. From this, future research can be done in order to enhance the existing intervention or to prompt new strategy in overcoming the problem.